RETRACTED: Physio-metabolic and clinical consequences of wearing face masks-Systematic review with meta-analysis and comprehensive evaluation - Kai Kisielinski; Oliver Hirsch; Susanne Wagner; Barbara Wojtasik; Stefan Funken; Bernd Klosterhalfen; Soumen Kanti Manna; Andreas Prescher; Pritam Sukul; Andreas Sönnichsen (Frontiers Media S.A., 2023)
BackgroundAs face masks became mandatory in most countries during the COVID-19 pandemic, adverse effects require substantiated investigation.MethodsA systematic review of 2,168 studies on adverse medical mask effects yielded 54 publications for synthesis and 37 studies for meta-analysis (on n = 8,641, m = 2,482, f = 6,159, age = 34.8 ± 12.5). The median trial duration was only 18 min (IQR = 50) for our comprehensive evaluation of mask induced physio-metabolic and clinical outcomes.ResultsWe found significant effects in both medical surgical and N95 masks, with a greater impact of the second. These effects included decreased SpO2 (overall Standard Mean Difference, SMD = −0.24, 95% CI = −0.38 to −0.11, p < 0.001) and minute ventilation (SMD = −0.72, 95% CI = −0.99 to −0.46, p < 0.001), simultaneous increased in blood-CO2 (SMD = +0.64, 95% CI = 0.31-0.96, p < 0.001), heart rate (N95: SMD = +0.22, 95% CI = 0.03-0.41, p = 0.02), systolic blood pressure (surgical: SMD = +0.21, 95% CI = 0.03-0.39, p = 0.02), skin temperature (overall SMD = +0.80 95% CI = 0.23-1.38, p = 0.006) and humidity (SMD +2.24, 95% CI = 1.32-3.17, p < 0.001). Effects on exertion (overall SMD = +0.9, surgical = +0.63, N95 = +1.19), discomfort (SMD = +1.16), dyspnoea (SMD = +1.46), heat (SMD = +0.70), and humidity (SMD = +0.9) were significant in n = 373 with a robust relationship to mask wearing (p < 0.006 to p < 0.001). Pooled symptom prevalence (n = 8,128) was significant for: headache (62%, p < 0.001), acne (38%, p < 0.001), skin irritation (36%, p < 0.001), dyspnoea (33%, p < 0.001), heat (26%, p < 0.001), itching (26%, p < 0.001), voice disorder (23%, p < 0.03), and dizziness (5%, p = 0.01).DiscussionMasks interfered with O2-uptake and CO2-release and compromised respiratory compensation. Though evaluated wearing durations are shorter than daily/prolonged use, outcomes independently validate mask-induced exhaustion-syndrome (MIES) and down-stream physio-metabolic disfunctions. MIES can have long-term clinical consequences, especially for vulnerable groups. So far, several mask related symptoms may have been misinterpreted as long COVID-19 symptoms. In any case, the possible MIES contrasts with the WHO definition of health.ConclusionFace mask side-effects must be assessed (risk-benefit) against the available evidence of their effectiveness against viral transmissions. In the absence of strong empirical evidence of effectiveness, mask wearing should not be mandated let alone enforced by law.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021256694, identifier: PROSPERO 2021 CRD42021256694.